Answer:
[tex]\textsf{Factored form}: \quad (a^2+4)(a-2)[/tex]
[tex]\textsf{Standard form}: \quad a^3-2a^2+4a-8[/tex]
Step-by-step explanation:
Given expression:
[tex]\dfrac{a^4-16}{a+2}[/tex]
Rewrite the exponent 4 as 2·2 and 16 as 4²:
[tex]\implies \dfrac{a^{2 \cdot 2}-4^2}{a+2}[/tex]
[tex]\textsf{Apply exponent rule} \quad a^{bc}=(a^b)^c[/tex]
[tex]\implies \dfrac{\left(a^2\right)^2-4^2}{a+2}[/tex]
[tex]\textsf{Apply the Difference of Two Squares Formula} \quad x^2-y^2=\left(x+y\right)\left(x-y\right):[/tex]
[tex]\implies \dfrac{(a^2+4)(a^2-4)}{a+2}[/tex]
Rewrite 4 in the second parentheses of the numerator as 2²:
[tex]\implies \dfrac{(a^2+4)(a^2-2^2)}{a+2}[/tex]
Apply the Difference of Two Squares Formula to (a² - 2²):
[tex]\implies \dfrac{(a^2+4)(a+2)(a-2)}{a+2}[/tex]
Cancel the common factor (a + 2):
[tex]\implies (a^2+4)(a-2)[/tex]
Expand:
[tex]\implies a^2(a-2)+4(a-2)[/tex]
[tex]\implies a^3-2a^2+4a-8[/tex]